Conceptual Model of an Expert System from Systematic Literature Review: Mental Health Screening in Pregnancy During the COVID-19 Pandemic - Dewi Nirmala Sari; Kemal N. Siregar; Hadi Pratomo (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background: The COVID-19 pandemic has triggered increased anxiety and depression in pregnant women, while the ability of health workers to detect early symptoms of anxiety and depression in pregnancy remains poor. Expert system transfers expert intelligence into a computer to provide prediction and interpretation of mental health screening results. This expert system provides easy access to mental health services for pregnant women and reduces the workload for health workers so that obstacles to access to services during and after the COVID-19 pandemic can be resolved. Objectives: We propose a conceptual model based on expert systems to allow early detection of anxiety and depression symptoms in pregnancy. Methods: In this model, a systematic literature review was used to choose the instrument for the expert system. Next, to assess symptoms of anxiety and depression in pregnancy, we designed a decision table and produced an algorithm in a screening chart using the rule-based expert system procedure. Results: Based on the results of the systematic literature review, there were 15 studies that had validated the screening instrument for symptoms of anxiety and depression in pregnant women. The results of the systematic review stated that the Edinburgh Postnatal Depression Scale (EPDS) had good sensitivity and specificity. Therefore, EPDS that be used in mental health screening based of expert system. Acquiring experts’ knowledge into a computer program, seven algorithms were designed on screening chart to detect anxiety and or depression symptoms in pregnancy. Conclusion: We illustrate that mental health screening in pregnancy using EPDS based on an expert system will provide accessibility of health services, accurate and fast results, a new approach for maternal mental health care, and avenues for future research.